1980
DOI: 10.1002/j.2050-0416.1980.tb06862.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Increased Steeping Temperatures on Enzyme Development in Malt

Abstract: Malts produced by steeping at 30°C for a total of 24 h including two air rests, frequently give the same results in routine analyses as do malts produced by steeping at 16°C for longer periods. However, the corresponding worts often filter more slowly under controlled laboratory conditions. The increased steeping temperatures can delay or reduce development of endopeptidase and p-glucan solubKase, but generally have little effect on the activity of o-amylase, carboxypeptidase, or endo-P-glucanase. The problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…The volume of wort collected in 30 minutes was taken as the filtration volume. [3][4][5][6][7][8][9][10][11][12][13] Endopeptidase activity was determined in green malt using a hordein substrate as described previously,1-3 and expressed as mg hordein solubiliscd/grain/hour. Carboxypeptidasc was measured using a N-carbobcnzoxy-Phe-Ala substrate,2 and free amino acids estimated by the 2,4,6-trinitrobenzcne sulphonic acid (TNBS) method.10 Activity was expressed as /<moles amino acid released/grain/hour.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of wort collected in 30 minutes was taken as the filtration volume. [3][4][5][6][7][8][9][10][11][12][13] Endopeptidase activity was determined in green malt using a hordein substrate as described previously,1-3 and expressed as mg hordein solubiliscd/grain/hour. Carboxypeptidasc was measured using a N-carbobcnzoxy-Phe-Ala substrate,2 and free amino acids estimated by the 2,4,6-trinitrobenzcne sulphonic acid (TNBS) method.10 Activity was expressed as /<moles amino acid released/grain/hour.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the findings of Müller et al (33,34), Baxter et al (13,26) and Reeves et al (25) found reduced lautering properties when applying higher steeping or germination temperatures. To exclude a negative influence of the accelerated malting on the lautering performance of the produced malt samples, an in-house laboratory lautering test was used (see 'Materials and methods' Figure 2.…”
Section: Resultsmentioning
confidence: 59%
“…Proteolytic modification is said to be reduced at higher germination temperatures resulting in lower free amino nitrogen (FAN) and soluble nitrogen content and thus decreased Kolbach indices, which can be insufficient for adequate yeast nutrition and foam stability in the final beer (12,16,21,28,29). In addition, Baxter and coworkers (13,26) and Reeves et al (25) observed an impaired filterability of mashes produced from warm steeped and germinated malt. On the other hand, a generally improved cytolytic modification could be observed when applying increased steeping and germination temperatures, as shown by several authors (10,12,21,22,(26)(27)(28)(29)31,34).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reduced protein-containing thiol groups engenders acceleration of wort filtration [10]. Muller [11] reported the production of hydrogen peroxide in mashes attendant to the oxidation of thiol groups.…”
Section: Thiol Oxidasementioning
confidence: 99%